Caracterização metalúrgica e mecânica de ligas de Ti-Nb-Sn laminadas a quente para uso biomédico - Sá, Dárcio Hersch Gomes de Souza (2013)
Titanium alloys with lower Young s modulus and free from toxic elements such as Al and V are being developed for biomedical applications. Ti-Nb-Sn alloys show great potential for this purpose. In this study, Ti-35Nb-XSn alloys (x = 2.5; 5.0; 7.5) were obtained from arc melting, homogenized, hot rolled and water quenched. The microstructures were characterized after each processing step by optical microscopy, scanning electron microscopy (SEM) and X-ray diffraction. Mechanical properties were determined by hardness tests, tensile tests, and ultrasonic technique to obtain the Young s modulus. These tests were performed in an attempt to compare the ductility and the strength to modulus ratio of the present alloys with those exhibited by other biomedical alloys whose properties are available in the literature. The mechanical behavior depends directly on the Sn amount as well as the phase constituents and it depends on the thermal and thermomechanical history to which the alloy was submitted. The hot rolled Ti-35Nb-2.5Sn alloy showed higher ductility and the strength to modulus ratio as high as those of some cold rolled Ti alloys.